The odyssey - Stowell, Louie (Usborne Pub Ltd; London, 2011)
The Odyssey by Louise Stowell is a retelling of Homer$1 (Bs epic, following Odysseus' perilous journey home after the Trojan War, filled with mythical creatures, gods, and enduring adventure.s